Effect of the different auxins and cytokinins in callus induction, shoot, root regeneration in sugarcane - K.GOPITHA; A.LAKSHMI BHAVANI; J.SENTHILMANICKAM (International Journal of Pharma and Bio Sciences, 2010)
Studies on micropropogation of callus culture was undertaken. In which expalnts were inoculated in MS medium fortified with various concentration of 2,4-D, auxin, cytokinin, sucrose at different pH level .The best callus induction was observed at 3.0mg/L, 2,4-D with 10% coconut milk (CM). Best regeneration of shoot was achieved when they were cultured on MS medium supplemented with BAP 1.0mg/L and IBA 0.5mg/L. Among the different media tested with 3mg/L NAA and 5% sucrose supplemented media proved best production of roots.